Biocontrol Activities of Olive Endophytic Bacteria Isolates Against Pseudomonas savastanoi - Avin O. Ali; Tavga S. Rashid (Polytechnic Journal)
Background and objectives: Olive knot disease caused by the phytopathogenic bacterium Pseudomonas savastanoi affects olive cultivation in both quality and quantity. Endophytic bacteria are candidates for biocontrol agents according to previous research. Methods: In this study we collected samples (leaves and galls) randomly for pathogen and endophytic bacteria isolation from the different olive growing areas around Erbil including (Qucha Blbas, Grdasor, Sami Abdulrahman Park, and College of Agricultural Engineering Sciences) on June - October 2021. Results: Forty-six isolates of endophytic bacteria were obtained and tested against P. savastanoi. The result indicated that five isolates showed growth inhibition of the pathogen among them two of the most effective isolates selected (Oq5 and Og2) with the pathogenic isolate molecularly identified using amplified 16S rDNA. The pathogenic isolate identified as P. savastanoi (Accession No. OP001734), isolate Oq5 P. fluorescens (Accession No. OP001733), and Og2 as Bacillus sp. (Accession No. OP001732). Also, their secondary metabolites extracted at different times of incubation and tested using the agar well diffusion method showed great inhibition of the pathogen. Both isolates showed the highest inhibition zone (25-26mm) after 10 days of incubation. Conclusions: Our results suggest that both endophytic bacteria isolate effective biocontrol of olive knot disease.